The Role of Managing Tourism Service Components in Promoting Religious Tourism-A Study of a Sample of Visitors to Visiting Cities - Taha Mahdi Mahmood (Genius Journals, 2023)
Our present era is witnessing an advanced global civilization with two wings (natural and human components), and the human elements are considered one of its most important fields, manifestations, and glory. The world's countries are keen to create and establish infrastructure and superstructures and tourist facilities that differ according to the types and types of tourism and to increase their number and diversify their savings, raise their level, make good use of them, and be proud of them. There is competition among the world's peoples for its display to attract tourists until these elements have become a standard for the sophistication of nations and a measure of their progress. Visiting it and knowing its details is evidence of the individual's cultural awareness and the focus of his social conversations.
Keywords: management; tourism components; tourism services